Preferred functionalization of metallic and small-diameter single-walled carbon nanotubes by nucleophilic addition of organolithium and -magnesium compounds followed by reoxidation - Wunderlich, David; Hauke, Frank; Hirsch, Andreas (Chemistry - A European Journal, 2008)
Covalent sidewall addition to single-walled nanotubes (SWNTs) of a series of organolithium and organomagnesium compounds (nBuLi, tBuLi, EtLi, nHexLi, nBuMgCl, tBuMgCl) followed by reoxidation is reported. The functionalized R-n-SWNTs were characterized by Raman and NIR emission spectroscopy. The reaction of SWNTs with organolithium and magnesium compounds exhibits pronounced selectivity: in general, metallic tubes are more reactive than semiconducting ones. The reactivity of SWNTs toward the addition of organometallic compounds is inversely proportional to the diameter of the tubes. This was determined simultaneously and independently for both metallic and semiconducting SWNTs. The reactivity also depends on the steric demands of the addend. Binding of the bulky t-butyl addend is less favorable than addition of primary alkyl groups. Significantly, although tBuLi is less reactive than, for example, nBuLi, it is less selective toward the preferred reaction with metallic tubes. This unexpected behavior is explained by fast electron transfer to the metallic SWNTs having low-lying electronic states close to the Fermi level, a competitive initial process. The NIR emission of weakly functionalized semiconducting SWNTs, also reported for the first time, implies interesting applications of functionalized tubes as novel fluorescent reporter molecules.
Keywords: carbon; electron transfer; nanotubes; nucleophilic addition; reactivity; selectivity